2007
DOI: 10.1111/j.1469-7580.2007.00774.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms in the formation of the medial longitudinal fascicle

Abstract: The first neurons in the vertebrate brain form a stereotypical array of longitudinal and transversal axon tracts, the early axon scaffold. This scaffold is thought to lay down the basic structure for the later, more complex neuronal pathways in the brain. The ventral longitudinal tract is pioneered by neurons located at the ventral midbrainforebrain boundary, which form the medial longitudinal fascicle. Recent studies have shed some light on the molecular mechanisms that control the development of the medial l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 48 publications
2
21
0
Order By: Relevance
“…Specification of neurons in the neural tube relies on combinations of bHLH and other transcription factors to activate or repress specific neurogenic programs. Homeobox genes, such as, Sax1 could play a role in specifying the nMLF subtypes [46], as gain of function of Sax1 results in an enlargement of the nMLF area [1]. However, other homeobox genes need to be found in order to explain the patterning of the neuronal populations of the early axon scaffold tracts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specification of neurons in the neural tube relies on combinations of bHLH and other transcription factors to activate or repress specific neurogenic programs. Homeobox genes, such as, Sax1 could play a role in specifying the nMLF subtypes [46], as gain of function of Sax1 results in an enlargement of the nMLF area [1]. However, other homeobox genes need to be found in order to explain the patterning of the neuronal populations of the early axon scaffold tracts.…”
Section: Discussionmentioning
confidence: 99%
“…It may be a different mechanism, as these populations of neurons are not distributed along specific axis. Sonic hedgehog (SHH), one of the main signalling molecules involved in neurogenesis patterning [38] is differentially expressed in the ventral forebrain [56] and mostly likely plays a critical role in the formation of the early axon scaffold tracts [1]. …”
Section: Discussionmentioning
confidence: 99%
“…1B,C,E,F,H,I). Pax6 is also expressed near the Nkx2-2-positive region in the developing midbrain (Ahsan et al, 2007). By combining ISH and IHC, we showed that Pax6 is expressed in a subset of Nkx2-2-positive cells in the ventral m4 domain at E11.5 (see Fig.…”
Section: Gata2 Andmentioning
confidence: 95%
“…The MLF is formed by neurons located at the ventral MFB that project their axons caudally. The tract runs as a loose bundle adjacent to the floor plate through midbrain and hindbrain towards the spinal cord (Ahsan et al, 2007). The LLF is made up of two groups of neurons: neurons in the mesencephalic nucleus of the trigeminus are found dorsally, close to the roof plate, and send their axons ipsilaterally to the trigeminal ganglion; neurons dispersed in the tectum mostly project contralaterally, growing their axons across the midline before joining the LLF to form the tectobulbar tract.…”
Section: The Longitudinal Guidance Systemmentioning
confidence: 99%
“…The early axon scaffold is made up of several longitudinal, transversal and commissural tracts including the medial longitudinal fascicle (MLF) and the posterior commissure (PC), both originating from the midbrain-forebrain border (MFB) region (reviewed in Ahsan et al, 2007). It has been hypothesised that the early axon scaffold sets up major pathways in the brain by forming substrates for future follower axons Kuwada, 1991, reviewed in Hjorth andKey, 2002).…”
Section: Introductionmentioning
confidence: 99%